2022
DOI: 10.21873/invivo.12938
|View full text |Cite
|
Sign up to set email alerts
|

Condylar Resorption Following Compressive Mechanical Stress in Rabbit Model - Association of Matrix Metalloproteinases

Abstract: Background/Aim: Idiopathic condylar resorption (ICR) is a morphological change of the condylar head that occurs following orthodontic treatment or orthognathic surgery. This complication is serious, as it can cause relapse after mandible treatment. The aim of this experimental study was to evaluate the mechanism of influence of condylar resorption on compressive mechanical stress in temporomandibular joint following a change in occlusal position by mandible advancement. Materials and Methods: An osteotomy proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Nogami et al 28 in an animal study demonstrated condylar resorption following compressive TMJ loading. Excessive loading may be related to parafunctional habits such as bruxism, clenching and gum chewing.…”
Section: Discussionmentioning
confidence: 97%
“…Nogami et al 28 in an animal study demonstrated condylar resorption following compressive TMJ loading. Excessive loading may be related to parafunctional habits such as bruxism, clenching and gum chewing.…”
Section: Discussionmentioning
confidence: 97%
“…MMP-3 has also been shown to be mechanosensitive; either a single injurious compression or cyclic supra-physiologic compression results in upregulation of MMP-3 and subsequent proteoglycan loss and cartilage degradation. [25][26][27][28] Mechanical injury with forces similar to what would be borne by the cartilage at the time of articular fracture has been shown to upregulate MMP-3 between 10-fold and 250-fold. 29,30 As such, future work is needed to better understand the mechanobiologic response to injury and the role of mechanobiologic mechanisms on PTOA progression.…”
Section: Discussionmentioning
confidence: 99%
“…Although the role of the articular disc remains unclear, the mandibular head may resorb over time in non-retrograde articular disc dislocation [ 14 ]. A recent study demonstrated that loading on the anterior surface of the condylar induced MMP-13, which is involved in articular cartilage degradation in the condylar head [ 15 ]. One possible treatment for ICR is surgical therapy for the condylar, but we did not choose this option.…”
Section: Discussionmentioning
confidence: 99%